The Role of Environmental Dialogues in Online Female Communities - Kelemen, Kata; Piskóti, Mariann (Marketing & Menedzsment, 2019)
Developing an environmentally conscious behaviour is a complex problem, which challenges the individual. To give up the evolved daily routine requires not only consciousness and positive attitude toward the issue, but adequate knowledge. Processing the information can be as complicated as acquiring it. To identify the appropriate behavioural alternatives external confirmation is needed. In this respect, new ways of communication - for instance in case of online communities - can play a significant role. Dialogues in these sites give opportunities for dissemination and negotiation of environmental knowledge. The study is based on the assumption that there are gender differences in approaching to environmental questions. This research focused on women. The article analyses what are the main topics and aspects that appear most often in the online female communities, and in what context they are discussed. The authors carried out a qualitative study using netnographic method.